Excitatory effects of calcitonin gene‐related peptide (Cgrp) on superficial sp5c neurons in mouse medullary slices - Zheng, Fang; Nixdorf-Bergweiler, Barbara; van Brederode, Johannes; Alzheimer, Christian; Meßlinger, Karl (International Journal of Molecular Sciences, 2021)
The neuromodulator calcitonin gene‐related peptide (CGRP) is known to facilitate noci-ceptive transmission in the superficial laminae of the spinal trigeminal nucleus caudalis (Sp5C). The central effects of CGRP in the Sp5C are very likely to contribute to the activation of central nocicep-tive pathways leading to attacks of severe headaches like migraine. To examine the potential im-pacts of CGRP on laminae I/II neurons at cellular and synaptic levels, we performed whole‐cell patch‐clamp recordings in juvenile mouse brainstem slices. First, we tested the effect of CGRP on cell excitability, focusing on neurons with tonically firing action potentials upon depolarizing current injection. CGRP (100 nM) enhanced tonic discharges together with membrane depolarization, an excitatory effect that was significantly reduced when the fast synaptic transmissions were phar-macologically blocked. However, CGRP at 500 nM was capable of exciting the functionally isolated cells, in a nifedipine‐sensitive manner, indicating its direct effect on membrane intrinsic properties. In voltage‐clamped cells, 100 nM CGRP effectively increased the frequency of excitatory synaptic inputs, suggesting its preferential presynaptic effect. Both CGRP‐induced changes in cell excitability and synaptic drives were prevented by the CGRP receptor inhibitor BIBN 4096BS. Our data provide evidence that CGRP increases neuronal activity in Sp5C superficial laminae by dose‐dependently promoting excitatory synaptic drive and directly enhancing cell intrinsic properties. We propose that the combination of such pre‐ and postsynaptic actions of CGRP might underlie its facilitation in nociceptive transmission in situations like migraine with elevated CGRP levels.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Calcitonin gene‐related peptide; Cell excitability; Excitatory postsynaptic currents; Migraine; Spinal trigeminal nucleus caudalis

Muscarinic Modulation of Morphologically Identified Glycinergic Neurons in the Mouse PreBötzinger Complex - Zheng, Fang; Nixdorf-Bergweiler, Barbara; Edelmann, Elke; van Brederode, Johannes; Alzheimer, Christian (Frontiers in Cellular Neuroscience, 2019)
The cholinergic system plays an essential role in central respiratory control, but the underlying mechanisms remain elusive. We used whole-cell recordings in brainstem slices from juvenile mice expressing enhanced green fluorescent protein (EGFP) under the control of the glycine transporter type 2 (GlyT2) promoter, to examine muscarinic modulation of morphologically identified glycinergic neurons in the preBötzinger complex (preBötC), an area critical for central inspiratory rhythm generation. Biocytin-filled reconstruction of glycinergic neurons revealed that the majority of them had few primary dendrites and had axons arborized within their own dendritic field. Few glycinergic neurons had axon collaterals extended towards the premotor/motor areas or ran towards the contralateral preBötC, and had more primary dendrites and more compact dendritic trees. Spontaneously active glycinergic neurons fired regular spikes, or less frequently in a "burst-like" pattern at physiological potassium concentration. Muscarine suppressed firing in the majority of regular spiking neurons via M2 receptor activation while enhancing the remaining neurons through M1 receptors. Interestingly, rhythmic bursting was augmented by muscarine in a small group of glycinergic neurons. In contrast to its heterogeneous modulation of glycinergic neuronal excitability, muscarine generally depressed inhibitory and excitatory synaptic inputs onto both glycinergic and non-glycinergic preBötC neurons, with a stronger effect on inhibitory input. Notably, presynaptic muscarinic attenuation of excitatory synaptic input was dependent on M1 receptors in glycinergic neurons and on M2 receptors in non-glycinergic neurons. Additional field potential recordings of excitatory synaptic potentials in the M2 receptor knockout mice indicate that glycinergic and non-glycinergic neurons contribute equally to the general suppression by muscarine of excitatory activity in preBötC circuits. In conclusion, our data show that preBötC glycinergic neurons are morphologically heterogeneous, and differ in the properties of synaptic transmission and muscarinic modulation in comparison to non-glycinergic neurons. The dominant and cell-type-specific muscarinic inhibition of synaptic neurotransmission and spiking may contribute to central respiratory disturbances in high cholinergic states.
EVALuna2:213484

Muscarinic Modulation of Morphologically Identified Glycinergic Neurons in the Mouse PreBötzinger Complex - Zheng, Fang; Nixdorf-Bergweiler, Barbara; Edelmann, Elke; van Brederode, Johannes; Alzheimer, Christian (Frontiers in Cellular Neuroscience, 2020)
The cholinergic system plays an essential role in central respiratory control, but the underlying mechanisms remain elusive. We used whole-cell recordings in brainstem slices from juvenile mice expressing enhanced green fluorescent protein (EGFP) under the control of the glycine transporter type 2 (GlyT2) promoter, to examine muscarinic modulation of morphologically identified glycinergic neurons in the preBötzinger complex (preBötC), an area critical for central inspiratory rhythm generation. Biocytin-filled reconstruction of glycinergic neurons revealed that the majority of them had few primary dendrites and had axons arborized within their own dendritic field. Few glycinergic neurons had axon collaterals extended towards the premotor/motor areas or ran towards the contralateral preBötC, and had more primary dendrites and more compact dendritic trees. Spontaneously active glycinergic neurons fired regular spikes, or less frequently in a “burst-like” pattern at physiological potassium concentration. Muscarine suppressed firing in the majority of regular spiking neurons via M2 receptor activation while enhancing the remaining neurons through M1 receptors. Interestingly, rhythmic bursting was augmented by muscarine in a small group of glycinergic neurons. In contrast to its heterogeneous modulation of glycinergic neuronal excitability, muscarine generally depressed inhibitory and excitatory synaptic inputs onto both glycinergic and non-glycinergic preBötC neurons, with a stronger effect on inhibitory input. Notably, presynaptic muscarinic attenuation of excitatory synaptic input was dependent on M1 receptors in glycinergic neurons and on M2 receptors in non-glycinergic neurons. Additional field potential recordings of excitatory synaptic potentials in the M2 receptor knockout mice indicate that glycinergic and non-glycinergic neurons contribute equally to the general suppression by muscarine of excitatory activity in preBötC circuits. In conclusion, our data show that preBötC glycinergic neurons are morphologically heterogeneous, and differ in the properties of synaptic transmission and muscarinic modulation in comparison to non-glycinergic neurons. The dominant and cell-type-specific muscarinic inhibition of synaptic neurotransmission and spiking may contribute to central respiratory disturbances in high cholinergic states.
CRIS-Team Scopus Importer:2020-02-04
Keywords: glycine; inhibitory neurotransmission; morphometric analysis; muscarinic acetylcholine receptors; preBötzinger complex

Release of CGRP from mouse brainstem slices indicates central inhibitory effect of triptans and kynurenate - Kageneck, Charlotte; Nixdorf-Bergweiler, Barbara; Meßlinger, Karl; Fischer, Michael (Journal of Headache and Pain, 2014)
CGRP is contained in a substantial proportion of unmyelinated trigeminal neurons innervating intracranial tissues. Previously, we have described a hemisected rodent scull preparation and later the intact trigeminal ganglion to measure stimulated CGRP release from trigeminal afferents.Here, we establish a preparation for examining CGRP release from central trigeminal terminals using single fresh slices of the mouse medullary brainstem.Basal and stimulated amount of CGRP substantially exceeded the detection level. Experiments were designed as matched pairs of at least six brainstem slices per animal. Stimulation with high potassium induced calcium-dependent and reversible CGRP release. Capsaicin stimulation of TRPV1 provoked concentration-dependent CGRP release. The anti-migraine drug naratriptan did not inhibit capsaicin-induced CGRP release from peripheral terminals but inhibited the release from brainstem slices. The glutamate antagonist kynurenate showed a similar pattern of site-specific inhibition of CGRP release.As observed earlier for other drugs used in the treatment of migraine this indicates that the central terminals in the spinal trigeminal nucleus may be the main site of action. The preparation allows evaluating the trigeminal brainstem as a pharmacological site of action.
EVALuna2:2458